Workshop: Coming together to leverage India’s national workfare program for resilient livelihoods for women - Bhubaneshwar consortium (International Food Policy Research Institute, 2024)
Public works programs have the potential to reduce poverty, provide resilience for workers to economic shocks, and improve infrastructure. The Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), India’s large national workfare program, has provided 3.07 billion person-days of work at a guaranteed minimum wage in the 2024 fiscal year alone, and received attention for both its scale and its role as a safety net for workers. The program also has significant potential to empower women. It guarantees equal pay for men and women and has a bottom-up participatory planning process in which anyone working in the program can propose the construction of assets that could improve their lives, livelihoods, and resilience to shocks.